A Book Review of â€œStrategic Financial Management : Managing for Value Creationâ€ by Dr. Prasanna Chandra - Kiran Kumar, K. V.; Balaji Rao, P. S. V. (Indian Journal of Finance, 2016)
Percolation of finance theory, frameworks, and concepts into corporate strategic corridors is presented with a macro, yet a step-by-step approach using the â€œEight Leversâ€ of â€œValue Octagonâ€. Each lever is interconnected with each other, symbolically and literally in the book - Strategic Financial Management: Managing For Value Creation - written by Dr. Prasanna Chandra. This book review explains the three broad sections of the text and explains the concept of the value octagon with highlights from the book. The aim of this book review was to appreciate the author's thought process of fitting the finance function into realms of strategy and thereby create a path for firms to approach the objective of value maximization. The thrust area of this book review was to further the discussions of strategy formulation and implementation, while finance is unseparated from the process. The review also discussed examples of real-life companies as well as opinions of various other authors and consulting groups on the subject-matter, in addition to the author's opinion. The review concluded that the value octagon and its eight value-driving levers proposed by the author encapsulate the broad areas of top management agenda in their pursuit of maximized intrinsic value.